Young elite athletes and social support: coping with competitive and organizational stress in "Olympic" competition - Kristiansen, E.; Roberts, G. C. (Scandinavian Journal of Medicine & Science in Sports, 2010)
Elite adolescent sport is a relatively unexplored research field. The purpose of this investigation was to examine how the Norwegian Olympic Youth Team (N=29) experienced competitive and organizational stress during the European Youth Olympic Festival in July 2007 and how they coped with the stressors. Participants were aged 14-17 and competed in handball, track and field, swimming, and judo. We used a qualitative methodology with interviews and open-ended questionnaires. Qualitative content analyses revealed that the athletes experienced competitive stressors because of the size and importance of the competition, and organizational stressors (e.g., housing, lining up for food, and transportation) exacerbated by the extreme heat during the Festival. The elite competitive experience was novel to all and overwhelming for some of the more "inexperienced" athletes. The athletes used cognitive coping strategies to some extent in addition to relying on different types of social support. The findings revealed the need for social support for adolescent athletes, and underlined the importance of a good coach-athlete relationship in order to perform well and enjoy the competitive experience.